2020
DOI: 10.1172/jci133953
|View full text |Cite
|
Sign up to set email alerts
|

Krabbe disease successfully treated via monotherapy of intrathecal gene therapy

Abstract: Conflict of interest: AMB is a beneficiary of a licensing agreement with Axovant Gene Therapies (royalties). DSO is an employee of and has equity holdings in Casma Therapeutics. ERB has received income from EScape Bio and Lysosomal Therapeutics Inc. (consulting). SJG has received research funding from Neurogene and Abeona and has received income from Neurogene (consulting and royalties) and Vertex Pharmaceuticals (consulting). CHV has received research funding from BioMarin Pharmaceuticals. SJG, EAL, CHV, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
45
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(48 citation statements)
references
References 47 publications
1
45
0
Order By: Relevance
“…In particular, it might be useful to establish the adequate dose of gene therapy, able to completely correct KD impairments. In support of this, a recent study showed that low but not high-dose gene therapy-treated dogs had visual system deficits [ 44 ].…”
Section: Discussionmentioning
confidence: 92%
“…In particular, it might be useful to establish the adequate dose of gene therapy, able to completely correct KD impairments. In support of this, a recent study showed that low but not high-dose gene therapy-treated dogs had visual system deficits [ 44 ].…”
Section: Discussionmentioning
confidence: 92%
“…To address these limitations, preclinical studies have aimed at developing targeted protocols that can efficiently deliver the vector while still achieving satisfactory disease correction. An increasingly recognized effective strategy is the use of intrathecal administration of gene therapy in KD (Reddy et al, 2011 ; Qin et al, 2012 ; Karumuthil-Melethil et al, 2016 ; Marshall et al, 2018b ; Bradbury et al, 2020 ). Multiple studies have achieved significant improvements in lifespan and motor function with protocols that deliver a single intrathecal gene therapy dose (Karumuthil-Melethil et al, 2016 ; Bradbury et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…An increasingly recognized effective strategy is the use of intrathecal administration of gene therapy in KD (Reddy et al, 2011 ; Qin et al, 2012 ; Karumuthil-Melethil et al, 2016 ; Marshall et al, 2018b ; Bradbury et al, 2020 ). Multiple studies have achieved significant improvements in lifespan and motor function with protocols that deliver a single intrathecal gene therapy dose (Karumuthil-Melethil et al, 2016 ; Bradbury et al, 2020 ). This study is an important step toward characterizing the full extent of KD pathology in the spinal cord and supports the importance of intrathecal delivery for treating KD with gene therapy.…”
Section: Discussionmentioning
confidence: 99%
“…AAV9 has also recently demonstrated effectiveness in a mouse model of Canavan disease (Gessler et al, 2017 ), which played a role in promoting the rAAV9- ASPA vector transitioning to a recent open-label clinical trial for Canavan disease ( CANaspire , ASPA Therapeutics). Finally, an exciting recent AAV9 finding is the success of AAV9- GALC in treating a canine model of globoid cell leukodystrophy or Krabbe disease, improving myelination and extending lifespan more than seven times beyond the typical life expectancy for model animals (Bradbury et al, 2020 ). However, AAV9 is not known to efficiently mediate significant transduction of oligodendrocyte lineage cells.…”
Section: Gene Transfer Therapy: Considerations In Leukodystrophiesmentioning
confidence: 99%